2014
DOI: 10.1002/ccd.25647
|View full text |Cite
|
Sign up to set email alerts
|

Successful percutaneous retrieval of a dislodged left atrial appendage occlusion device with double transseptal sheaths and biopsy bioptome

Abstract: A 64-year-old woman underwent left atrial appendage occlusion with an Amplatzer Cardiac Plug device. Displacement of the device was detected on day 1 with transesophageal echocardiographic checking. The device became dislodged and flitted in the left atrium after unsuccessful retrieval with a snare and 12 Fr steerable transseptal sheath. A double transseptal sheath technique was then attempted. The flitting device was stabilized by one 12 Fr steerable transseptal sheath and successfully retrieved with a biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…Potential causal mechanisms for embolization were reported in only four cases including device undersizing in two cases , device oversizing in one case , and conversion from AF to sinus rhythm in another case . Major adverse events related to device embolization occurred in three patients (9.7%): one case of internal bleeding during percutaneous retrieval, one case of device‐related Ao cusps damage requiring Ao valve replacement and 1 case of death due to cardiogenic shock.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential causal mechanisms for embolization were reported in only four cases including device undersizing in two cases , device oversizing in one case , and conversion from AF to sinus rhythm in another case . Major adverse events related to device embolization occurred in three patients (9.7%): one case of internal bleeding during percutaneous retrieval, one case of device‐related Ao cusps damage requiring Ao valve replacement and 1 case of death due to cardiogenic shock.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of 20 studies reporting 31 cases of device embolization were identified including 2 multi‐center randomized trials, 4 multi‐center registries, 6 single‐center registries and 9 case reports. There were 13 reported cases with WM and 18 cases with ACP . Studies reporting embolization of WM and ACP are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In another case, an acutely dislodged ACP device in the LA was percutaneously retrieved with double transseptal sheaths and a biopsy bioptome. 7 The most difficult aspect of percutaneous retrieval of a migrated device is stabilizing the device flitting in the LA cavity and aligning its distal screw with the retrieval tool. As described in our first case, we used a steerable ablation catheter to stabilize the moving ACP device against the LA wall and a U-shaped 6-Fr EBU catheter to achieve good alignment between the distal screw of the ACP device and a gooseneck snare loop.…”
Section: Discussionmentioning
confidence: 99%
“…Migrated devices can be removed by engaging one of the short tips with a snare or by engaging the mesh itself using biopsy forceps, and then collapsing the plug inside a larger sheath for removal. 14,15 Endothelialization of the migrated device can make the retrieval very difficult and potentially traumatic. 16…”
Section: Potential Challenges Of Using the Avpmentioning
confidence: 99%